Regularities of epoxidized alkyl oleates ring-opening reactions with alcohols, water and organic acids in the presence of commercial sulfonated resins as catalysts - Davitadze, David Z.; Konovalov, Sergiy V. (V.P. Kukhar Institute of Bioorganic Chemistry and Petrochemistry of the National Academy of Sciences of Ukraine, 2024)
Current paper deals with the use of sulfonated resins, distinguished by the porous structure (macroreticular Purolite CT275 and gel-type CU-2-8ChS), as solid acid catalysts for syntheses of perspective components of biolubricants via oxirane ring-opening reactions of fatty epoxides with water (hydrolysis), ethanol and i-propanol (alkoxylation), and levulinic and oleic acids (acylation). Epoxidized ethyl and i-propyl oleates as ring opening substrates were synthesized from used cooking oil. Reactions were carried out in batch reactor for 3 h at 100 °C under stirring with epoxide: resin acid sides molar ratio 1 : 0.05. Reagent to epoxide ratio was 10 : 1 (alkoxylation, hydrolysis) or 1.5 : 1 (acylation). Products composition was determined by GC, conversion and selectivity were calculated. Number of side ring-opening reaction were revealed, main of which were isomerization to ketone and dimerization. General observation is that porous Purolite CT275 provides higher conversion, but facilitates side processes. Non-porous CU-2-8-CHs provided notably higher selectivity (up to 90 % for hydroxyl esters in ethoxylation), but with many-times slower conversion, especially in case of alkoxylation with secondary alcohol. In hydrolysis, water soaked cationites did not provide any conversion, while epoxide introduction first on catalyst made transformation possible. Acylation proceeded in a great extent without separate catalyst and was accompanied by dimerization, while isomerization was not observed. Gel-type resin provided only negligible growth of conversion and selectivity. Porous resin enhanced the conversion, but mainly by side reactions intensification. Cyclohexane as solvent facilitated slightly selective catalyst-free acylation, but with significant conversion drop. Purolite CT275 in ethyl levulinate media favored the ring opening of epoxide with ketone function, yielding ketal-type product.